Citation Analysis of the Use of Online Journals Published by ISI Yogyakarta in the Final Project Work of ISI Yogyakarta Students - Agustiawan Agustiawan (ABDI PUSTAKA: Jurnal Perpustakaan dan Kearsipan, 2023)
Citation Analysis of the Use of Online Journals Published by ISI Yogyakarta in the Final Project of ISI Yogyakarta Students. This study aims to determine the level of citation of the use of online journals published by ISI Yogyakarta in the final project of ISI Yogyakarta students (Graduates Period 1 of 2022). This research is a type of quantitative research and is descriptive. The method used in this research is to use the form of documentation. This research was conducted at the UPT ISI Yogyakarta Library by accessing the final work of students who have been included in the list of graduates for the period one of the year 2022 and have carried out independent uploads of their final position in the library repository via http://digilib.isi.ac.id. In this study, the authors determined that the research population was the last project of 382 graduate students for the period one of the year 2022 and will use purposive sampling, namely a sampling technique with specific considerations, namely those that have been uploaded independently in the ISI Yogyakarta library repository which at the time of data collection there were 260 who had already been uploaded. Do a self-upload. In this study, the documentation method is used, namely verifying the data of online journal articles published by ISI Yogyakarta, which students cited in compiling their final work (Graduates Period 1 the Year 2022). From the results of this study, it is known that 12.6% (33 people) of students use journals published by ISI Yogyakarta as a reference in compiling the final project of graduating students for period one, the year 2022, at ISI Yogyakarta. From this percentage, it can be concluded that the usability of journals published by ISI Yogyakarta is deficient because it is included in the 0-20% scale range. The results of this study can be used as a joint evaluation material between journal managers, lecturers, and librarians to promote further the use of online journals published at ISI Yogyakarta to be a reference in compiling students' final work at ISI Yogyakarta. This is important so that science and research results in the journal will continue to develop. Besides that, the value and usefulness of the journal will be increasingly felt to support the preparation of the final project at ISI Yogyakarta. Penelitian ini bertujuan untuk mengetahui tingkat sitasi penggunaan jurnal online terbitan ISI Yogyakarta dalam karya tugas akhir mahasiswa ISI Yogyakarta. Penelitian ini merupakan jenis penelitian kuantitatif dan bersifat deskriptif. Metode yang digunakan dalam penelitian ini adalah menggunakan metode dokumentasi. Penelitian ini dilakukan di UPT Perpustakaan ISI Yogyakarta dengan mengakses karya tugas akhir mahasiswa yang telah masuk dalam daftar wisudawan periode 1 tahun 2022 dan telah melaksanakan unggah mandiri karya tugas akhirnya dalam repository perpustakaan melalui http://digilib.isi.ac.id. Dalam penelitian ini penulis menetapkan populasi penelitian adalah karya tugas akhir mahasiswa wisudawan periode 1 tahun 2022 sebanyak 382 dan menggunakan sampling purposive yakni teknik penentuan sampel dengan pertimbangan tertentu yakni yang sudah unggah mandiri di repository perpustakaan ISI Yogyakarta yang pada saat pengambilan data ada 260 yang sudah melakukan unggah mandiri. Di dalam penelitian ini menggunakan metode dokumentasi yaitu memverifikasi data artikel jurnal online terbitan ISI Yogyakarta yang disitasi oleh para mahasiswa dalam menyusun karya tugas akhir (Wisudawan Periode 1 Tahun 2022). Dari hasil penelitian ini diketahui bahwa ada 12,6% (33 orang) mahasiswa yang menggunakan jurnal terbitan ISI Yogyakarta sebagai rujukan dalam menyusun karya tugas akhir mahasiswa wisudawan periode 1 tahun 2022di ISI Yogyakarta. Dari persentase tersebut dapat disimpulkan bahwa tingkat keterpakaian jurnal terbitan ISI Yogyakarta termasuk kategori sangat rendah karena masuk dalam rentang skala 0-20%. Hasil penelitian ini dapat menjadi bahan evaluasi bersama antara pengelola jurnal, para dosen, dan pustakawan untuk lebih mempromosikan penggunaan jurnal online yang terbit di ISI Yogyakarta untuk menjadi rujukan dalam menyusun karya tugas akhir para mahasiswa di ISI Yogyakarta. Hal ini penting dilakukan agar ilmu pengetahuan dan hasil penelitian yang ada di jurnal akan semakin berkembang, selain itu nilai kemanfaatan jurnal akan semakin dirasakan untuk menunjang penyusunan karya tugas akhir di ISI Yogyakarta.